2022
DOI: 10.31234/osf.io/q5wt2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Suspecting Foul Play When It Is Objectively There: The Association of Political Orientation with General and Partisan Conspiracy Beliefs as a Function of Corruption Levels

Abstract: Recent research has showed that people with right-wing political orientations and political extremists are more likely to harbor conspiracy beliefs. Utilizing a multisite dataset (23 countries, N > 20,000), we show that corruption moderates how political orientation predicts conspiracy beliefs. We found that (1) the difference between left- and right-wingers in terms of adopting a conspiracy mindset is attenuated in countries with high corruption; and (2) left-wingers are more likely to believe left-win… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…If the expectation of dishonesty is not ungrounded, then an increase in education would not be strongly related to an increase in trust in science and scientists since one would have good enough reasons not to trust in such contexts. Past research showed that country-level corruption is a significant factor in predicting conspiracy beliefs (Alper, 2021;Alper et al, 2021;Alper & Imhoff, 2022), and the negative association between education and conspiracy beliefs is weaker in high corruption countries because conspiracy beliefs are relatively more plausible in these contexts (Alper, 2021). In the current research, we similarly argue that the association of education with trust in science and scientists would be weaker in countries with high corruption.…”
Section: Highly Corrupt Countriessupporting
confidence: 59%
See 2 more Smart Citations
“…If the expectation of dishonesty is not ungrounded, then an increase in education would not be strongly related to an increase in trust in science and scientists since one would have good enough reasons not to trust in such contexts. Past research showed that country-level corruption is a significant factor in predicting conspiracy beliefs (Alper, 2021;Alper et al, 2021;Alper & Imhoff, 2022), and the negative association between education and conspiracy beliefs is weaker in high corruption countries because conspiracy beliefs are relatively more plausible in these contexts (Alper, 2021). In the current research, we similarly argue that the association of education with trust in science and scientists would be weaker in countries with high corruption.…”
Section: Highly Corrupt Countriessupporting
confidence: 59%
“…This novel finding is worth discussing in more detail: Why does corruption weaken the relationship between education and trust in science and scientists? Perhaps, recent work assessing the role of corruption within the conspiracy beliefs literature (Alper, 2021;Alper & Imhoff, 2022;Alper et al, 2021) may provide important insights into this question. In three large-scale cross-cultural samples, Alper (2021) found that the negative relationship between education and conspiracy beliefs was moderated by countrylevel corruption, such that this relationship only emerged in low corruption countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Distrust not only in institutions but also in other people (e.g., Abalakina-Paap, Stephan, Craig, & Gregory, 1999;Douglas & Sutton, 2018;Goertzel, 1994;van Prooijen & Acker, 2015), media (e.g., Bruder & Kunert, 2021;Su, Lee, Xiao, Li, & Shu, 2021), and science (e.g., Constantinou, Kagialis, & Karekla, 2020;Erceg et al, 2020) are positively related to the beliefs in conspiracy theories. As corruption is negatively related to social trust (Richey, 2010;Rothstein & Eek, 2009), people living in highly corrupt places would be expected to be more suspicious of others, and such suspicion would breed conspiracy beliefs (see Alper & Imhoff, 2022).…”
Section: The Social Context and The Conspiracy Beliefsmentioning
confidence: 99%
“…Moreover, the relationship between conflicts and conspiracy beliefs can be inferred based on previous evidence showcasing a relationship between constructs closely associated with intergroup conflict on the one hand, and support for or acceptance of conspiracy theories, on the other hand. For example, acceptance or support for conspiracy theories was found to be related to prejudice (Imhoff & Bruder, 2014), intergroup aggression (Imhoff et al, 2021), social exclusion (Poon et al, 2020), oppression and relative deprivation (Crocker et al, 1999), corruption (Alper, 2021; Alper et al, 2021; Alper & Imhoff, 2022), and inequality (Pearson & Hornsey, 2022; Salvador Casara et al, 2022). However, it should be noted that although these constructs are all related to violent conflicts, they do not fully capture the overall intensity of conflicts.…”
mentioning
confidence: 99%